Impact of the COVID-19 Pandemic on Colorectal Cancer Surgery: Surgical Outcomes and Tumor Characteristics in a Multicenter Retrospective Cohort - Sahin, Emrah; Akbulut, Sami; Ogut, Zeki; Yilmaz, Serkan; Dalda, Yasin; Tuncer, Adem; Kucukakcali, Zeynep (Mdpi, 2025)
Background: Colorectal cancer (CRC) is a leading cause of cancer-related mortality worldwide. The COVID-19 pandemic disrupted healthcare systems globally, raising concerns about delays in CRC diagnosis and treatment, and their potential negative effects on surgical outcomes. However, the extent of this impact remains uncertain. Aim: To compare the clinical characteristics, treatment strategies, and outcomes of CRC patients between the Pre-COVID-19 and COVID-19 Era groups, and to identify independent predictors of metastasis and mortality. Methods: This retrospective multicenter study included 397 CRC patients who underwent surgical treatment between 1 July 2018, and 1 August 2021, at three tertiary medical centers. Patients were divided into two groups: Pre-COVID-19 (n = 213) and COVID-19 Era (n = 184). Demographic data, tumor characteristics, surgical approach, postoperative complications, and survival outcomes were analyzed. Logistic regression analysis was conducted to identify independent predictors of metastasis and mortality. Results: The median age was 64 years (95% CI: 63-66), with 59.2% being male. Compared to the Pre-COVID-19 group, patients in the COVID-19 Era had significantly larger tumors (p < 0.001), with a significantly higher total LN retrieved (p = 0.006), more advanced T-stage (p = 0.007), higher N2 lymph node involvement (p = 0.027), and poorer tumor differentiation (p = 0.030). Intestinal perforation was more frequent in the Pre-COVID-19 group (p = 0.042). Multivariate analysis revealed increased odds of mortality associated with the positive LN retrieved (OR: 1.14; p = 0.001), moderate tumor differentiation (OR: 2.99; p = 0.043), poor differentiation (OR: 4.57; p = 0.023), undifferentiated histology (OR: 6.95; p = 0.028), intestinal obstruction (OR: 2.67; p = 0.007), intestinal perforation (OR: 11.76; p < 0.001), and distant metastasis (OR: 2.86; p = 0.008). Regarding metastasis, elevated preoperative CEA (OR: 1.02; p = 0.002), lymph node involvement (OR: 4.87; p = 0.002), and perineural invasion (OR: 2.17; p = 0.033) were independently associated with increased odds of metastasis. Conclusions: Although overall survival did not differ significantly between groups, patients treated during the COVID-19 Era exhibited more advanced histopathological characteristics, including a higher proportion of T4 tumors, increased N2 lymph node involvement, and poorer differentiation grades. Despite no significant differences in postoperative complications between groups, it is noteworthy that preoperative intestinal perforation was less frequent in the COVID-19 Era cohort.
Keywords: COVID-19 pandemic; colorectal cancer; emergency surgery; tumor characteristics; surgical outcomes